Replication of Measles Virus: Distinct Species of Short Nucleocapsids in Cytoplasmic Extracts of Infected Cells - Kiley, Michael P. (1974)
Cytoplasmic extracts of Vero cells infected with wild-strain Edmonston measles virus were found to contain two and probably three distinct species of nucleocapsids. Species sedimenting at 200 and 110S contained RNA which sedimented at 50 and 16 to 18S, respectively. The third nucleocapsid species which sedimented at 170S was not present in all experiments and was not characterized in detail. Essentially all 200 and 170S, as well as a portion of the 110S, nucleocapsids were membrane associated and probably present in part in cell-associated virions. Five of six plaque purified strains derived from wild-type Edmonston virus produced only 200S nucleocapsids. One of these five plaque-purified strains subsequently produced both 200 and 110S nucleocapsids after being passaged by using undiluted inocula. These results suggest that measles virus may produce distinct classes of defective virus containing short nucleocapsids and subgenomic viral RNA.